An arthroscopic and electromyographic study of painful shoulders in elite gymnasts - Caraffa, A.; Cerulli, G.; Rizzo, A.; Buompadre, V.; Appoggetti, S.; Fortuna, M. (Knee surgery, Sports Traumatology. Arthroscopy, 1996)
Shoulder problems are common in overhead sports like baseball, basketball and volleyball. Although gymnastics also includes overhead activities, there are few reports about shoulder problems in this sports activity. During the time period 1992-1995 we treated five young competitive gymnasts for shoulder pain. Arthroscopy revealed that they were all suffering from SLAP lesions or other labral pathology, although they had never dislocated their shoulders. These injuries have not been described earlier in connection with gymnastics. In a survey of 13 gymnasts in an elite club, we found that six (46%) complained about shoulder pain. Since four of these athletes explained that their shoulder pain started acutely during ring exercises in suspension while one suffered a slower onset with pain also during parallel bar exercises, we undertook an electromyographic study of the shoulder musculature of three normal elite gymnasts during exercises on the parallel bars and rings. We found that during the ring exercises in suspension there was a "critical phase" during which the muscle activity around the shoulder was very low, leading to great articular stresses. This might explain the occurrence of labral lesions like the SLAP lesions in this type of athlete. If shoulder pain in elite gymnasts does not respond to rest and physical therapy over 2-3 months, a shoulder arthroscopy should be considered.